Religious Moderation and Digital Citizenship in Indonesia: Examining State Narratives and Muslim Netizens’ Engagement - Theguh Saumantri; Ghina Amaliyah Sholihah; Afiyah Qurrota A’yun; Mohamad Faiq; Zulmi Ramdani (Analisa: Journal of Social Science and Religion, 2026)
The transformation of the digital ecosystem has reshaped how religious moderation is produced, distributed, and practiced within Indonesian Muslim society. Traditionally, religious moderation has been positioned as a normative discourse constructed by the state to maintain social harmony and stability. However, within participatory digital spaces, this discourse is reinterpreted by netizens who produce diverse meanings. This study aims to analyze the construction of religious moderation by the state in digital spaces, its interpretation and practice by Muslim netizens, as well as the dynamics of digital communication network structures. The research employs a descriptive qualitative approach. Data were collected through digital observation and documentation, while data analysis was conducted using thematic analysis. The empirical data were collected from official government digital platforms and Muslim netizens' interactions on Twitter (X) and YouTube. The findings indicate that state discourse tends to be normative, uniform, and top-down, emphasizing values such as tolerance, social harmony, and stability. In contrast, the practice of religious moderation among netizens is participatory and dynamic, characterized by polarization, interpretive debates, and the contestation of religious identities. The structure of digital communication networks reveals fragmentation and the presence of echo chambers, where interactions are more dominant within homogeneous groups. The study concludes that religious moderation in digital spaces has transformed from a policy discourse into a contested discourse, functioning as a discursive arena collectively produced by both state and societal actors.